Continuous zirconium oxide fiber with ionic gel coating and preparation method of continuous zirconium oxide fiber
By forming an ion gel coating prepared by a low eutectic solvent on the surface of the zirconia fiber, the problems of poor clustering and brittleness in the three-dimensional braiding process are solved, and the wear resistance and self-lubricating characteristics of the fiber are improved. Improves weaving efficiency and product quality.
Patent Information
- Application Number
- CN202411382082.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-30
AI Technical Summary
During the three-dimensional braiding process, continuous zirconia fibers have poor clustering and high brittleness, resulting in low weaving efficiency and poor product quality.
The ionic gel coating prepared by eutectic solvent is uniformly formed on the surface of zirconia fibers. The preparation of a mixed solution of ramie fiber treatment and ionic gel prepolymerization solution is achieved by combining UV-induced polymerization technology to achieve self-healing and high-quality ionic gels through ramie fiber treatment and preparation of ionic gels through ramie fiber treatment and ionic gel prepolymerization solution. Mechanical properties.
The friction coefficient of zirconia fiber is improved, its wear resistance and self-lubricating properties are enhanced, the mechanical properties and processing properties of the fiber are improved, and the weavability and weaving efficiency of the fiber are improved.
Smart Images

Figure CN119465639A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of continuous inorganic ceramic fiber new materials, and in particular relates to a continuous zirconia fiber with an ion gel coating and a preparation method thereof. Background Art
[0002] Zirconia fiber has the characteristics of high temperature resistance, oxidation resistance, low heat capacity and light weight, and has huge application demand in aerospace, military defense and modern advanced industrial fields. However, continuous zirconia fiber has the disadvantages of poor bundling and large single filament brittleness. During the three-dimensional weaving process, frequent mechanical friction between multiple layers of yarn causes yarn damage, resulting in zirconia fiber bundles fuzzing, splitting and even breaking, reducing its weaving efficiency.
[0003] As an emerging material, ion gels have shown great application potential in artificial skin, soft robots, biomedical engineering and other fields. However, the performance loss caused by water loss when exposed to air, the loss of flexibility caused by water crystallization at low temperature, and water corrosion at the contact interface between hydrogel and metal electrode have greatly limited the practical application of hydrogels. In order to improve the above shortcomings, researchers have developed ion gels with ionic liquids as solvents, which are non-corrosive to metal electrodes and the solvents are non-volatile, but the cost is high and the toxicity is high. Deep eutectic solvents are a new type of ionic liquid with low volatility, biodegradability and low cost. They have received widespread attention in the field of separation and dissolution, but their great potential in the preparation of eutectic gels has not been deeply developed, and their mechanical properties are not satisfactory due to the shielding effect of the solvent.
[0004] At present, there is no ion gel coating preparation technology for improving the weavability of continuous zirconia fibers in China. Therefore, it is of great significance to modify the surface of long narrow diameter / low surface energy zirconia fibers with ion gel coatings with excellent environmental stability, high mechanical properties and self-healing properties to improve the bundling of zirconia fibers, reduce the friction coefficient of zirconia fibers, reduce the amount of hair during processing, and adapt to the requirements of zirconia fiber performance in the later three-dimensional texture forming process such as weaving, laying and winding. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing continuous zirconia fibers with ion gel coating.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0009] (1) Ramie fiber treatment: soaking the pretreated ramie fiber in a mixed solution of 2.0-3.0 wt% silane coupling agent, 2-4 wt% deionized water and 93-96 wt% anhydrous ethanol for 1-3 h, adjusting the pH value of the solution, and washing and drying after the reaction is completed;
[0010] (2) Preparation of ion gel prepolymer mixed solution: The low eutectic solvent and ramie fiber are mixed evenly and stirred at 70-90° C. for 1-2 h. After cooling to room temperature, a photoinitiator is added and stirred evenly to obtain an ion gel prepolymer mixed solution.
[0011] (3) preparing continuous zirconia fibers with ion gel coating: immersing the continuous zirconia fibers in an ion gel prepolymer solution, extracting the fibers after 1 to 5 minutes and initiating polymerization under UV conditions to obtain continuous zirconia fibers with ion gel coating;
[0012] Wherein, the added amount of the ramie fiber is 0-1.5% of the total mass of the low eutectic solvent.
[0013] As a preferred embodiment of the method for preparing the continuous zirconia fiber with ion gel coating of the present invention, the pretreatment is to mechanically crush the ramie fiber, pass it through a 100-mesh sieve, and then perform ball milling and fine crushing treatment.
[0014] As a preferred solution of the method for preparing the continuous zirconium oxide fiber with ion gel coating of the present invention, the length of the pretreated ramie fiber is 40-50 μm.
[0015] As a preferred embodiment of the method for preparing continuous zirconia fiber with ion gel coating of the present invention, the silane coupling agent includes one or more of KH-550 silane coupling agent, vinyl triethoxy silane, vinyl trimethoxy silane, and vinyl tri(β-methoxyethoxy) silane.
[0016] As a preferred solution of the method for preparing the continuous zirconia fiber with ion gel coating of the present invention, the amount of ramie fiber added to the ion gel prepolymer solution is 1% of the total mass of the low eutectic solvent.
[0017] As a preferred embodiment of the method for preparing continuous zirconia fiber with ion gel coating of the present invention, the photoinitiator includes one or more of 2959 (2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone), 4-dimethylamino-ethyl benzoate, 2-isopropylthioxanthone, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester, and 2-hydroxy-2-methyl-1-phenylpropiophenone.
[0018] As a preferred embodiment of the method for preparing the continuous zirconia fiber with ion gel coating of the present invention, the low eutectic solvent includes one or more of choline chloride, acrylic acid, and hydroxyethyl acrylate.
[0019] As a preferred embodiment of the method for preparing the continuous zirconia fiber with ion gel coating of the present invention, the zirconia fiber is a single-strand fiber.
[0020] As a preferred embodiment of the method for preparing the continuous zirconia fiber with ion gel coating of the present invention, the UV irradiation intensity is 50 to 100 W and the time is 10 to 60 s.
[0021] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a continuous zirconia fiber with an ion gel coating.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention uses a novel, designable low eutectic solvent to prepare ion gel, overcoming the problems of high cost and toxicity of organic solvent ion gel.
[0024] (2) Ramie fibers, which are abundant in raw materials, biodegradable and low in cost, are added to a low eutectic solvent, and the resulting ion gel has excellent self-healing and mechanical properties. Ramie fibers are treated with a coupling agent to improve the dispersion of the fibers in the prepolymer solution.
[0025] (3) The ion gel achieves multifunctional integration, has good flexibility, high transparency, self-healing and excellent mechanical properties, and has broad application prospects; it has the advantages of easy preparation, green environmental protection and low cost; it provides a new idea for the preparation of ion gels that combine abundant raw materials, biodegradability and low cost with excellent mechanical properties.
[0026] (4) By uniformly forming an ion gel coating on the surface of the zirconia fiber, the friction coefficient of the fiber is reduced, the wear resistance of the brittle continuous zirconia fiber is effectively improved, and the fiber has certain lubrication properties. At the same time, the phenomenon of fuzz and broken fibers after fiber friction is improved, and the mechanical properties and processing properties of the fiber are improved, thereby improving the weavability and weaving efficiency of the continuous zirconia fiber and the product quality of the zirconia fabric. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:
[0028] Figure 1 Mechanical properties of ion gels prepared from AA, HEA and ChCl at different curing times.
[0029] Figure 2 The fracture stress and elongation at break of ion gels prepared from AA, HEA and ChCl at different curing times.
[0030] Figure 3 Toughness and Young's modulus of ion gels prepared from AA, HEA and ChCl at different curing times.
[0031] Figure 4 Mechanical properties of ion gels prepared with different ratios of AA, HEA and ChCl.
[0032] Figure 5 The fracture stress and elongation of ion gel prepared at different ratios of AA, HEA and ChCl; x-y It refers to the ion gel prepared by using AA, HEA and ChCl, x refers to the amount of ChCl, and y refers to the molar ratio of HEA to AA.
[0033] Figure 6 It is a schematic diagram of the preparation of the ion gel of the present invention and a schematic diagram of the network microstructure.
[0034] Figure 7 This is a schematic structural diagram of the continuous zirconia fiber with ion gel coating prepared in the present invention; wherein: 1. ion gel coating; 2. zirconia fiber. DETAILED DESCRIPTION
[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0037] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0038] The raw materials used in the present invention are all commercially available unless otherwise specified.
[0039] The performance of the material prepared in the embodiment of the present invention was tested as follows:
[0040] The tensile breaking strength test is measured in accordance with GB / T3362-2005; the stiffness test is carried out in accordance with GB / T7690.4-2013 Test method for yarn of reinforcing materials Part 4: Determination of stiffness; the wear rate test is carried out in accordance with FZ / T01058-1999 Test method for yarn wear resistance - reciprocating roller method; the coefficient of friction (COF) test is carried out using a UMT-Tribolab friction and wear testing machine.
[0041] Example 1
[0042] The present invention provides a method for preparing a deep eutectic solvent ion gel:
[0043] (1) Preparation of ion gel prepolymer mixed solution: 0.5 g of choline chloride (ChCl), 1.33 g of acrylic acid (AA) and 2.67 g of hydroxyethyl acrylate (HEA) were mixed at 80°C and stirred at 300 r / min for 1 h until a colorless and transparent solution was formed. After cooling to room temperature, 0.05 g of UV initiator (2959) was added and mixed evenly to obtain an ion gel prepolymer mixed solution.
[0044] (2) Pour the ion gel prepolymer mixed solution into a polytetrafluoroethylene mold, place the mold under an 80W UV light source, and form an ion gel after curing for 10 seconds.
[0045] Example 2
[0046] The difference from Example 1 is that the curing time is adjusted to 20 seconds, and the rest of the preparation process is the same as that of Example 1 to obtain an ion gel.
[0047] Example 3
[0048] The difference from Example 1 is that the curing time is adjusted to 30 seconds, and the rest of the preparation process is the same as that of Example 1 to obtain an ion gel.
[0049] Example 4
[0050] The difference from Example 1 is that the curing time is adjusted to 40 seconds, and the rest of the preparation process is the same as that of Example 1 to obtain an ion gel.
[0051] Example 5
[0052] The difference from Example 1 is that the curing time is adjusted to 50 seconds, and the rest of the preparation process is the same as that of Example 1 to obtain an ion gel.
[0053] Depend on Figures 1 to 3 From the analysis, it can be seen that curing for 40 seconds in Example 4 is the best solution.
[0054] Example 6
[0055] The difference from Example 4 is that in step (1), an ion gel prepolymer mixed solution is prepared: 0.5 g ChCl, 2.0 g acrylic acid and 2.0 g HEA are mixed at 80° C. and stirred at 300 r / min for 1 h until a colorless and transparent solution is formed. After cooling to room temperature, 0.05 g UV initiator (2959) is added and mixed evenly to obtain an ion gel prepolymer mixed solution.
[0056] Example 7
[0057] The difference from Example 4 is that in step (1), an ion gel prepolymer mixed solution is prepared: 0.5 g ChCl, 0.8 g acrylic acid and 3.2 g HEA are mixed at 80° C. and stirred at 300 r / min for 1 h until a colorless and transparent solution is formed. After cooling to room temperature, 0.05 g UV initiator (2959) is added and mixed evenly to obtain an ion gel prepolymer mixed solution.
[0058] Example 8
[0059] The difference from Example 4 is that in step (1), an ion gel prepolymer mixed solution is prepared: 0.5 g ChCl, 1.0 g acrylic acid and 3.0 g HEA are mixed at 80° C. and stirred at 300 r / min for 1 h until a colorless and transparent solution is formed. After cooling to room temperature, 0.05 g UV initiator (2959) is added and mixed evenly to obtain an ion gel prepolymer mixed solution.
[0060] Figure 4 The mechanical properties of ion gels prepared with different ratios of AA, HEA and ChCl; Figure 5 The fracture stress and elongation at break of the ion gel prepared with different ratios of AA, HEA and ChCl are shown in Example 4 as the optimal ratio for preparing the ion gel of the deep eutectic solvent.
[0061] Example 9
[0062] This embodiment provides a method for preparing a continuous zirconia fiber with an ion gel coating, referring to Figure 6 , specifically:
[0063] S1: Ramie fiber treatment: The washed and dried ramie fiber was mechanically crushed and sieved with a 100 mesh screen. 15g of the sieved ramie fiber powder and 80 zirconium dioxide balls with a diameter of 10mm were weighed and added into the zirconium dioxide tank of the planetary ball mill. The ball milling was carried out at a speed of 500r / min for 5h. The ball milling interval was 5min for every 10min of ball milling. The length of the obtained ramie fiber was 42-47um. 10g of ramie fiber was soaked in a mixed solution of 2.5wt% silane coupling agent (KH-550), 2wt% deionized water and 95.5wt% anhydrous ethanol for 1h, and 0.5mol / L acetic acid solution was added dropwise while stirring to adjust the pH value of the solution to 3.5. After the reaction was completed, it was washed with deionized water to remove the silane coupling agent and ethanol adsorbed on the surface and dried at 60℃.
[0064] S2: Preparation of ion gel prepolymer mixed solution: 0.5g choline chloride, 1.33g acrylic acid, 2.67g hydroxyethyl acrylate and ramie fiber are mixed evenly (the ramie fiber content is 1.0% of the total mass of the low eutectic solvent), stirred at room temperature for 1h, cooled to room temperature, and then 0.05g UV initiator (2959) is added to obtain an ion gel prepolymer mixed solution.
[0065] S3: The continuous zirconia fiber is immersed in the ion gel prepolymer solution obtained in S2, and then extracted after 5 minutes and polymerized under 80WUV light for 40 seconds to obtain a continuous zirconia fiber with an ion gel coating. The structural diagram is shown in FIG. Figure 7 shown.
[0066] In this embodiment, repeated friction under a load of 1N causes breakage after about 300 abrasions, resulting in scratches and debris.
[0067] Example 10
[0068] The difference between this embodiment and embodiment 9 is that the dosage of ramie fiber is adjusted to 0 of the total mass of the low eutectic solvent, and the rest of the preparation process is the same as that of embodiment 9, and continuous zirconia fiber with ion gel coating is obtained.
[0069] In this embodiment, repeated friction under a load of 1N causes breakage after about 200 abrasions, resulting in scratches and debris.
[0070] Embodiment 11
[0071] The difference between this embodiment and embodiment 9 is that the dosage of ramie fiber is adjusted to 0.5% of the total mass of the low eutectic solvent, and the rest of the preparation process is the same as that of embodiment 9, and continuous zirconia fiber with ion gel coating is obtained.
[0072] In this embodiment, repeated friction under a load of 1N causes breakage after approximately 230 wear cycles, resulting in scratches and debris.
[0073] Example 12
[0074] The difference between this embodiment and embodiment 9 is that the dosage of ramie fiber is adjusted to 1.5% of the total mass of the low eutectic solvent, and the rest of the preparation process is the same as that of embodiment 9, and continuous zirconia fiber with ion gel coating is obtained.
[0075] In this embodiment, repeated friction under a load of 1N causes breakage, scratches and debris, after approximately 287 wears.
[0076] Comparative Example 1
[0077] Original fiber.
[0078] The performance of the materials obtained in the above embodiments and comparative examples was tested, and the comparison results with those of Example 9 are shown in Table 1.
[0079] Table 1
[0080]
[0081] As can be seen from Table 1, compared with the original continuous zirconia fiber, under the condition of a coating thickness of about 0.12 mm, the wear rate of the fiber is reduced by 2.1% to 6.7%, the friction coefficient is reduced by 2.3% to 13.1%, the wear resistance is significantly improved, and the self-lubricating property is achieved to a certain extent; the tensile properties of the fiber are increased by 0.6% to 3.2%, and the stiffness is reduced, which helps to improve the fiber damage and breakage caused by bending deformation during the weaving of the continuous zirconia fiber. Adjusting the addition amount of ramie fiber has a significant effect on the performance of the continuous zirconia fiber. This is because ramie fiber has high surface activity and high aspect ratio, and its surface has many hydrophilic groups that react and combine with polar groups in the ion gel. Strong ionic bonds and multiple hydrogen bonding forces increase the mechanical strength of the ion gel. In summary, the preferred addition amount of ramie fiber is 1.0%.
[0082] The present invention uses a new, designable low eutectic solvent to prepare ion gel, which overcomes the problems of high cost and toxicity of organic solvent ion gel. Ramie fiber, which is abundant in raw materials, biodegradable and low in cost, is added to the low eutectic solvent, and the ion gel obtained by polymerization has excellent self-healing and mechanical properties; the ramie fiber is treated with a coupling agent to improve the dispersibility of the fiber in the prepolymer solution. The ion gel realizes multifunctional integration, has good flexibility, high transparency, self-healing and excellent mechanical properties, and has broad application prospects; it has the advantages of easy preparation, green environmental protection and low cost; it provides a new idea for the preparation of ion gel that combines abundant raw materials, biodegradability and low cost with excellent mechanical properties.
[0083] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a continuous zirconia fiber with an ion gel coating, characterized in that: include, Ramie fiber treatment: soaking the pretreated ramie fiber in a mixed solution of 2.0-3.0wt% silane coupling agent, 2-4wt% deionized water and 93-96wt% anhydrous ethanol for 1-3h, adjusting the pH value of the solution simultaneously, and washing and drying after the reaction is completed; Preparation of ion gel prepolymer mixed solution: low eutectic solvent and ramie fiber are mixed evenly and stirred at 70-90° C. for 1-2 hours, and after cooling to room temperature, a photoinitiator is added and stirred evenly to obtain an ion gel prepolymer mixed solution. Preparation of continuous zirconia fiber with ion gel coating: soaking the continuous zirconia fiber in ion gel prepolymer solution, extracting it after 1 to 5 minutes and initiating polymerization under UV conditions to obtain continuous zirconia fiber with ion gel coating; Wherein, the added amount of the ramie fiber is 0-1.5% of the total mass of the low eutectic solvent.
2. The method for preparing a continuous zirconia fiber with an ion gel coating according to claim 1, characterized in that: The pretreatment is to grind the ramie fiber mechanically, pass it through a 100-mesh sieve, and then perform ball milling and grinding treatment.
3. The method for preparing continuous zirconia fiber with ion gel coating according to claim 1, characterized in that: The length of the pretreated ramie fibers is 40 to 50 μm.
4. The method for preparing continuous zirconia fiber with ion gel coating according to claim 1, characterized in that: The silane coupling agent includes one or more of KH-550 silane coupling agent, vinyl triethoxy silane, vinyl trimethoxy silane, and vinyl tri(β-methoxyethoxy) silane.
5. The method for preparing continuous zirconia fiber with ion gel coating according to claim 1, characterized in that: In the ion gel prepolymer solution, the amount of ramie fiber added is 1% of the total mass of the low eutectic solvent.
6. The method for preparing continuous zirconia fiber with ion gel coating according to claim 1, characterized in that: The photoinitiator includes one or more of 2959 (2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone), 4-dimethylamino-ethyl benzoate, 2-isopropylthioxanthone, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester, and 2-hydroxy-2-methyl-1-phenylpropiophenone.
7. The method for preparing continuous zirconia fiber with ion gel coating according to claim 1, characterized in that: The low eutectic solvent includes one or more of choline chloride, acrylic acid, and hydroxyethyl acrylate.
8. The method for preparing continuous zirconia fiber with ion gel coating according to claim 1, characterized in that: The zirconia fiber is a single-strand fiber.
9. The method for preparing continuous zirconia fiber with ion gel coating according to claim 1, characterized in that: The UV irradiation intensity is 50-100W and the time is 10-60s.
10. A continuous zirconia fiber with an ion gel coating prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Coating for improving mechanical properties of zirconium oxide fibers and preparation method of coating
CN112411179A
Self-healing, anti-freezing and self-adhesive conductive ion hydrogel with birefringence characteristic as well as preparation method and application of self-healing, anti-freezing and self-adhesive conductive ion hydrogel
CN115368509A
Preparation method of super-elastic and high-conductivity cellulose-based eutectic gel
CN116903887A
Controlled release delivery device comprising an organosol coat
EP2007360A1